Dried aquatic macrophytes are floating egg banks and potential dispersal vectors of ostracods (Crustacea) from pleuston communities - Rosa, J.; Martens, K.; Higuti, J. (Hydrobiologia, 2022)
In aquatic ecosystems, such as Neotropical floodplains, it is common to find dried aquatic mac-rophytes along the margins of various environments (e.g. lakes and rivers) during the dry season. Here, we evaluate the potential of dried Eichhornia crassipes as a dispersal vector of ostracod resting eggs by assessing the abundance, richness and beta diversity of the dor-mant associated fauna. We test two hypotheses: (1) that the roots of E. crassipes shelter and disperse ostracod resting eggs and (2) that the abundance, richness and beta diversity of dormant assemblages will increase In aquatic ecosystems, such as Neotropical floodplains, it is common to find dried aquatic mac-rophytes along the margins of various environments (e.g. lakes and rivers) during the dry season. Here, we evaluate the potential of dried Eichhornia crassipes as a dispersal vector of ostracod resting eggs by assessing the abundance, richness and beta diversity of the dor-mant associated fauna. We test two hypotheses: (1) that the roots of E. crassipes shelter and disperse ostracod resting eggs and (2) that the abundance, richness and beta diversity of dormant assemblages will increase